2007
DOI: 10.3151/jact.5.181
|View full text |Cite
|
Sign up to set email alerts
|

Structural Design of 80-Story RC High-Rise Building Using 200 Mpa Ultra-High-Strength Concrete

Abstract: This paper presents the design of an 80-story reinforced concrete (RC) high-rise building using 200 MPa ultra-high-strength concrete. Static nonlinear push over analyses, Level-1 and Level-2 nonlinear earthquake response analyses and nonlinear wind response analyses were carried out. Based on the three-dimensional static nonlinear analyses of the building subjected to design earthquake loading in two principal directions, the obtained maximum axial load ratio for the first story columns of 200 MPa compressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The issue includes another five papers, providing more information on HSC and HPC (Jinnai et al 2007;Kimura et al 2007a;Kimura et al 2007b;Kuroiwa et al 2007;Tanimura et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…The issue includes another five papers, providing more information on HSC and HPC (Jinnai et al 2007;Kimura et al 2007a;Kimura et al 2007b;Kuroiwa et al 2007;Tanimura et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…To address the outlined issues, high‐strength concrete has been employed in the base stories to resist large forces and moments accumulated over the building's height 3–5 . The application of high‐performance, fiber‐reinforced concrete has been particularly studied in earthquake‐resistant structures with a focus on critical regions, such as base of shear walls 6‐8 .…”
Section: Introductionmentioning
confidence: 99%
“…To address the outlined issues, high-strength concrete has been employed in the base stories to resist large forces and moments accumulated over the building's height. [3][4][5] The application of high-performance, fiber-reinforced concrete has been particularly studied in earthquake-resistant structures with a focus on critical regions, such as base of shear walls. [6][7][8] The experimental test results have indicated that such composite walls can introduce superior strength, displacement capacity, and damage tolerance, compared to their NSC counterparts.…”
mentioning
confidence: 99%
“…29 A preliminary design of a 40-story building made of UHPC and a comparison with the conventional concrete solution was also carried out. 30 Kimura et al 31 studied the dynamic properties of an 80-floor building with a 200 MPa UHPC.…”
Section: Introductionmentioning
confidence: 99%